2020
DOI: 10.1016/j.ajic.2020.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and associated factors of hand hygiene compliance in a pediatric tertiary hospital

Abstract: Background: The objective is to know the evolution of the Degree of Compliance with Recommendations (DCR) on hand hygiene (HH) and its associated factors in the pediatric care areas (PCAs) of a tertiary hospital. Methods: Observational, cross-sectional study, repeated over time, with direct observation of the DCR on HH during the daily activity of health care workers. Over 13 years, 9226 HH opportunities were observed. Associations between DCR, PCA and other variables (eg, age, sex, and professional position) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(61 reference statements)
0
4
0
1
Order By: Relevance
“…In the present study, compliance was higher in the operation theatre for pediatric patients. Healthcare workers in pediatric patient care settings are known to have higher HH compliance [ 10 , 16 ]. One reason may be that pediatric patient populations rely greatly on hands-on-care [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, compliance was higher in the operation theatre for pediatric patients. Healthcare workers in pediatric patient care settings are known to have higher HH compliance [ 10 , 16 ]. One reason may be that pediatric patient populations rely greatly on hands-on-care [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cabe destacar, que respecto a las oportunidades en las que se realiza la higiene de manos y considerando los 5 momentos de la OMS (1: antes de tocar al paciente, 2: antes de realizar una tarea limpia/aséptica, 3: después del riesgo de exposición a líquidos corporales, 4: después de tocar al paciente, 5: después del contacto con el entorno del paciente), existen diferencias significativas entre ellas. Hemos visto que el grado de cumplimiento es más alto en aquellas actividades que tienen lugar en los momentos "después" (3, 4 y 5 de la OMS), mientras que es menor en los momentos "antes" (1 y 2 de la OMS)(8) . Esto pone de manifiesto la necesidad de un cambio de paradigma en los profesionales sanitarios que consideran la higiene de manos como una forma de protegerse después de entrar en contacto con el paciente.…”
unclassified
“…We found that HH moment 5, after touching the patient's surroundings, showed the least overall compliance. Although we did not assess the reasons for poor compliance, studies have shown that poor compliance is affected by behavioral factors, awareness of HCWs to HH opportunity, availability of alcohol hand rubs, and overall altitude, thus emphasizing a need for continued training, use of posters and supply of appropriate alcohol at bed-side for HH [45][46][47].…”
Section: Discussionmentioning
confidence: 99%